The genomics of desmoplastic small round cell tumor reveals the deregulation of genes related to DNA damage response, epithelial–mesenchymal transition, and immune response. Issue 1 (28th November 2018) - Devecchi, Andrea; De Cecco, Loris; Dugo, Matteo; Penso, Donata; Dagrada, Gianpaolo; Brich, Silvia; Stacchiotti, Silvia; Sensi, Marialuisa; Canevari, Silvana; Pilotti, Silvana
Abstract: Background: Desmoplastic small round cell tumor (DSRCT) is a rare, aggressive, and poorly investigated simple sarcoma with a low frequency of genetic deregulation other than an Ewing sarcoma RNA binding protein 1 ( EWSR1 )‐Wilm's tumor suppressor ( WT1 ) translocation. We used whole‐exome sequencing to interrogate six consecutive pre‐treated DSRCTs whose gene expression was previously investigated. Methods: DNA libraries were prepared from formalin‐fixed, paraffin‐embedded archival tissue specimens following the Agilent SureSelectXT2 target enrichment protocol and sequenced on Illumina NextSeq 500. Raw sequence data were aligned to the reference genome with Burrows–Wheeler Aligner algorithm. Somatic mutations and copy number alterations (CNAs) were identified using MuTect2 and EXCAVATOR2, respectively. Biological functions associated with altered genes were investigated through Ingenuity Pathway Analysis (IPA) software. Results: A total of 137 unique somatic mutations were identified: 133 mutated genes were case‐specific, and 2 were mutated in two cases but in different positions. Among the 135 mutated genes, 27% were related to two biological categories: DNA damage‐response (DDR) network that was also identified through IPA and mesenchymal–epithelial reverse transition (MErT)/epithelial–mesenchymal transition (EMT) already demonstrated to be relevant in DSRCT. The mutated genes in the DDR network were involved in various steps of transcription and particularly affected pre‐mRNA. Half of these genes encoded RNA‐binding proteins or DNA/RNA‐binding proteins, which were recently recognized as a new class of DDR players. CNAs in genes/gene families, involved in MErT/EMT and DDR, were recurrent across patients and mostly segregated in the MErT/EMT category. In addition, recurrent gains of regions in chromosome 1 involving many MErT/EMT gene families and loss of one arm or the entire chromosome 6 affecting relevant immune‐regulatory genes were recorded. Conclusions: The emerging picture is an extreme inter‐tumor heterogeneity, characterized by the concurrent deregulation of the DDR and MErT/EMT dynamic and plastic programs that could favour genomic instability and explain the refractory DSRCT profile.